Respostas

A melhor resposta!
2013-12-12T15:10:42-02:00
X²-2x=x+4
x²-2x-x=4
x²-3x-4=0
Δ = b² -4ac
Δ = (-3)² -4 *1 * (-4)
Δ = 9 + 16
Δ = 25
x' = (-b + √∆)/ 2a
(-(-3) + 5)/2 * 1
(3 + 5)/2
8/2= 4
x'' = (-b - √∆)/ 2a
(-(-3) - 5)/2 * 1
(3 - 5)/2
-2/2= -1

S= {4,-1}
1 5 1
2013-12-12T15:14:41-02:00
X²-2x=x+4 ----------> x²-2x-x-4
x² - 3x -4 = 0
a= 1
b= -3
c= -4
Δ = b²-4ac
Δ = (-3)² - 4.1.-4
Δ = 25

x'= -b + √Δ/2a
x'= 4

x''= -b - √Δ/2a
x''= -1

C.E.:
x²-3x-4=0

4²-3.4-4=0
16-16=0 (v)

-1²-3.-1-4=0
1+3-4=0
4-4=0 (v)

S={4;-1}
1 5 1